2013
DOI: 10.1007/s12668-013-0083-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hapten–Protein Conjugates: Antibody Generation and Immunoassay Development for Pesticides Monitoring

Abstract: The generation of specific and sensitive antibodies against small molecules is greatly dependent upon the characteristics of the hapten–protein conjugates. In the present study, we report a new fluorescence-based method for the characterization of hapten–protein conjugates. The method is based on an effect promoted by hapten–protein conjugation density upon the fluorescence intensity of the intrinsic tryptophan chromophore molecules of the protein. The proposed methodology is applied to quantify the hapten–pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…An important step in anti-hapten antibody development is verification of the success of conjugation and the conjugation degree of the hapten to carrier proteins. The use of mass spectrometer MALDI-TOF (Matrix-assisted laser desorption/ionization, time-of-flight) has been described previously [ 26 ] as being able to meet these needs, and a similar approach was used here. The MALDI-TOF results revealed that the MPA-AP and MPA-HSA had conjugation degrees of ~5 and ~29 MPA/protein, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…An important step in anti-hapten antibody development is verification of the success of conjugation and the conjugation degree of the hapten to carrier proteins. The use of mass spectrometer MALDI-TOF (Matrix-assisted laser desorption/ionization, time-of-flight) has been described previously [ 26 ] as being able to meet these needs, and a similar approach was used here. The MALDI-TOF results revealed that the MPA-AP and MPA-HSA had conjugation degrees of ~5 and ~29 MPA/protein, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the most prominent method for generating antibodies relies on the immunization of animals with an immunogenic analyte. Small analytes are typically non-immunogenic due to their low molecular weight, thus, rendering the generation of suitable antibodies difficult, and while methods have been developed to remediate this drawback, these procedures are costly and time consuming [ 13 , 14 ]. Aptamers, on the other hand, do not suffer from this limitation and can be generated against a wide range of analytes, such as ions [ 15 ], small molecules [ 16 ], proteins [ 17 ], viruses [ 18 ], bacteria [ 19 ] and even whole cells [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The substance is introduced to the animals to generate an immune response—immunization. However, not all compounds are immunogenic, requiring high-cost and laborious methods to obtain suitable antibodies [ 30 , 31 , 32 ]. In contrast, aptamers can practically be developed for all sorts of chemicals, ranging from single ions to microorganisms [ 6 , 7 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%